The Attitudes of Women Towards Family Planning Practices in Reproductive Health in Mukono, Kauga Village, Uganda - Rapha Naume (Uganda Christian University, 2023)
This study explored the attitudes of women towards family planning practices in reproductive health in Kauga Village, Mukono, Uganda. The specific objectives of the study included; examining the factors that influence women's attitudes towards family planning services, assessing the knowledge and attitudes of women regarding family planning, and identifying the challenges women face while accessing family planning services. The research employs a cross-sectional study design to gather comprehensive insights into these aspects. The findings of the study revealed that the factors influencing women's attitudes towards family planning services are economic factors, health concerns, partner's opinions, and religious beliefs. barriers such as lack of information or access, cultural norms, and fear of side effects, personal experiences, cultural and religious beliefs, and peer influence,access to information and the ease of accessing services were deemed essential, emphasizing the importance of making family planning information and services readily available, especially in rural areas. The study assessed knowledge and attitudes regarding family planning among respondents. While a majority of participants reported having a moderate understanding of family planning, there was room for improvement, with a significant proportion rating their knowledge as fair or poor. Most respondents recognized family planning as a positive practice for women's health, highlighting its significance in improving women's well-being. Various sources of information, including healthcare providers, family planning clinics, community health workshops, and online resources, contributed to knowledge dissemination, underscoring the importance of utilizing diverse channels for education. The study indicated the challenges faced by women when accessing family planning services in Kauga Village, Mukono such as limited access to family planning clinics in rural areas, stigma and judgment from healthcare providers, long waiting times, limited contraceptive options, cultural and religious beliefs discouraging family planning, high costs, lack of privacy, and concerns about side effects. To improve family planning practices and support in the community, recommendations include enhancing accessible family planning clinics, sensitizing healthcare providers to reduce stigma, expanding contraceptive options, and launching community-based educational programs to raise awareness and dispel myths. In conclusion, if implemented collaboratively by stakeholders including healthcare providers, community organizations, and policymakers, have the potential to enhance family planning awareness, education, and accessibility in Kauga Village, ultimately leading to improved reproductive health outcomes and overall well-being for women in the community.
This is a dissertation.